Geomorphologic parameters based prioritization of hilly sub-watersheds using remote sensing and geographical information system - KANDPAL, HIMANSHU; KUMAR, ANIL; REDDY, C. P.; MALIK, ANURAG (Journal of Soil and Water Conservation, 2020)
This study was undertaken to prioritize hilly sub-watersheds based on geomorphologic parameters obtained using remote sensing (RS) and geographical information system (GIS) in the Chaukhutia watershed of Ramganga River basin in state of Uttarakhand, India. The Chaukhutia watershed was delineated and further sub-divided into eighteen sub-watersheds using RS and GIS techniques. The geomorphologic parameters used for prioritization are based on linear/aerial aspects namely bifurcation ratio, drainage density, stream frequency, texture ratio and mean length of overland flow; along with shape parameters such as form factor, circularity ratio, compactness coefficient and elongation ratio. On the basis of geomorphologic parameters, ranking of each parameter was done and finally a compound (average) rank was calculated for each sub-watershed. The sub-watershed SW2 was found to have the lowest compound value of 5.8, indicating that it is subjected to the maximum soil erosion. Therefore, the highest priority rank ‘first’ was given to SW2 for implementing appropriate soil and water conservation measures for its development. Similarly, all the sub-watersheds were awarded ranks and prioritized for better planning and management in the region.